The modern naval fortress: an additional sea denial option for coastal states. Issue 1 (2nd January 2018) - Wu, Shang-su
Abstract: As fixed facilities, naval fortresses seem unlikely to be important in a sea denial strategy which is usually about mobility, but new defence technologies and the changing geostrategic environment may revive the concept of the fortress. Extended ranges of anti-ship means allow onshore firepower to engage enemies over distance, even beyond the economic exclusive zones where most maritime territorial disputes occur. In the face of size limits on missile warheads that constrain their destruction of hardened targets, various active and passive defence technologies against missiles can enhance the survivability of onshore fortresses. Furthermore, onshore locations give fortresses the advantage of being unsinkable and able to accommodate greater energy and firepower capacity in contrast to vessels, as well as other mobile platforms. The onshore nature of fortresses also gives a different political meaning to being attacked, for the clear violation of sovereignty, as opposed to vessels and aircraft in a disputed space. However, the fact those fortresses are not invincible means cooperation with other existing capabilities still necessary. The case of Vietnam demonstrates how fortresses could strengthen the inferior defence capability of a coastal state vis-à-vis. a stronger sea power.